2014
DOI: 10.5455/2349-3933.ijam20141104
|View full text |Cite
|
Sign up to set email alerts
|

Rhinosporidiosis: a clinicopathological study from a Rural Tertiary Health Care Centre, Bihar, India

Abstract: Background: Rhinosporidiosis is a chronic granulomatous infection characterized by a bleeding polypoidal mass which commonly affects the nose and nasopharynx. The disease is caused by Rhinosporidium seeberi. It grows in stagnant water and is thought to be transmitted to human by infected soil and water by gaining entry through traumatized epithelium and mucosa of nose and nasopharynx. It has a high incidence of occurrence among rural population. Surgical excision is the treatment of choice. Methods: Totally, 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 4 publications
1
12
0
5
Order By: Relevance
“…16,21 People belonging to lower socioeconomic status were found to be more affected. 12,15,17 In the current study, the majority of the cases was from rural areas (81.82%), and most of the affected individuals were students, followed by laborers. The major portion of cases belonged to the lower socioeconomic status.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…16,21 People belonging to lower socioeconomic status were found to be more affected. 12,15,17 In the current study, the majority of the cases was from rural areas (81.82%), and most of the affected individuals were students, followed by laborers. The major portion of cases belonged to the lower socioeconomic status.…”
Section: Discussionmentioning
confidence: 52%
“…Previous studies have found that patients affected with the disease had history of taking baths in ponds, rivers, tanks, lakes, reservoirs, and wells. 4,12,[15][16][17][18][19][20][21] All cases in the present study also had history of pond bathing. This shows the constant exposure of the patients to infected water sources.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In comparison to present study, similar results were observed in a study from Bihar. [9] Present study findings suggest that person with nasal mass and practice of pond bathing with poor hygiene, Rhinosporidium seeberi infection can be the primary cause. However, among the negative cases differential diagnosis must be followed for inverted papilloma and non-invasive fungal sinusitis.…”
Section: Discussionmentioning
confidence: 54%
“…Dapsone is given as an adjuvant to surgical treatment to prevent recurrence. 11,14 Definitive diagnosis is by histopathology which show many round, thick walled sporangia in the submucosa containing sporangiospores. 4 Objectives of the Study 1.…”
Section: Introductionmentioning
confidence: 99%